Pemanfaatan Media Sosial Sebagai Proses Digital Marketing Untuk Peningkatan Nilai Jual Di UMKM Kerajinan Bambu - Herlangga Turna Cahyantoro (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Digital marketing is a marketing concept that is widely used in this modern era. Many manufacturers choose to use digital marketing in their marketing process because marketing goods through digital media saves energy and costs. In the process of digital marketing or digital marketing, a high creative process is needed because digital marketing requires producers to make content as attractive as possible for consumers to see and be interested in the products offered. In this case we examine how useful the application of digital marketing is in the marketing process of Bamboo MSMEs located in the Kepanjen Kidul Village, Kepanjen Kidul District, Blitar City. The method used is descriptive method with a qualitative approach. The descriptive method is used to describe the efforts of UMKM Bambu